The Interregional Impact of Fiscal Decentralization in Indonesia: Inter Regional Social Accounting Matrix Model - Utama, Satria; Brodjonegoro, Bambang P. S. (Jurnal Ekonomi dan Pembangunan Indonesia, 2003)
-